2020
DOI: 10.1016/j.ijpddr.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Route of administration influences the concentration of ivermectin reaching nematode parasites in the gastrointestinal tract of cattle

Abstract: An animal trial was conducted to measure the concentrations of ivermectin occurring in abomasal and small intestinal contents and mucosa, and in the target parasites ( Ostertagia ostertagi and Cooperia oncophora ) following administration by subcutaneous, oral and pour-on routes. Twenty-five steers were infected with ivermectin-resistant isolates of O . ostertagi and C . oncophora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Therefore, it is vital that drugs are administered by a veterinarian or a skilled person, and supervised by a veterinarian. In a study on cattle, where efficiency and plasma profiles were compared after moxidectin and lately in ivermectin administration in three different routes (oral, infection, and pour-on), significant differences were found between efficiency and drug administration routes [48][49][50][51]. These studies highlight how important it is to apply drugs correctly and use the correct protocol of drug introduction.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it is vital that drugs are administered by a veterinarian or a skilled person, and supervised by a veterinarian. In a study on cattle, where efficiency and plasma profiles were compared after moxidectin and lately in ivermectin administration in three different routes (oral, infection, and pour-on), significant differences were found between efficiency and drug administration routes [48][49][50][51]. These studies highlight how important it is to apply drugs correctly and use the correct protocol of drug introduction.…”
Section: Discussionmentioning
confidence: 98%
“…However, MOX concentrations in the host dropped significantly compared to IVM and abamectin despite similar plasma levels within 2 days post treatment, suggesting that drug elimination may vary between different ML derivatives [ 62 ]. In Ostertagia ostertagi , a cattle parasite dwelling on the surface of the abomasal mucosa and feeding by sucking on the mucosa, IVM levels in the worms were shown to correlate with IVM concentration in the abomasal mucosa and were maximised by subcutaneous drug application [ 63 ]. These findings would support that parasite nematode IVM susceptibility is also increased by feeding.…”
Section: Discussionmentioning
confidence: 99%
“…These findings would support that parasite nematode IVM susceptibility is also increased by feeding. In the same study, IVM levels in the cattle parasite, Cooperia oncophora , which dwells in the small intestine, correlated well with intestinal content, and parasite exposure was maximised by oral drug application [ 63 ]. Overall, the study by Leathwick et al highlights how parasite exposure considerably differs between parasitic species with regard to their biology [ 63 ], a concept that can also be extended to the different developmental stages, e.g., migrating/histotropic or hypobiotic stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different routes of IVM administration in cattle, such as oral, topical (pour-on), and injectable (Leathwick et al 2020), but the conventional injectable formulation has now been considerably replaced for the topical in livestock practices (Laffont et al 2003). After administration, IVM is partially metabolized by livestock (Chiu et al 1990), regardless of the route of administration, the drug is mainly eliminated via feces, and to a lesser extent, less than 2%, in urine (Gonzalez Canga et al 2009), and up to 5% excretion has been reported during the lactation period in milk (Chicoine et al 2007).…”
Section: Introductionmentioning
confidence: 99%